Interactive Learning Media for Sasak Local Content Subject for Grade 4 Elementary School Based on Adobe Flash (A Case Study at SDN 4 Keruak) - Muhammad Nasrullah; Muhammad Khulaimi; Abdul Azis (Institute of Educational, Research, and Community Service)
The development of instructional media plays a very important role in the field of education. The purpose of developing this instructional media is to make the teaching and learning process more effective, engaging, and easy to implement. Based on observations at SDN 4 Keruak, learning activities still use manual instructional media, such as books, written materials, and other teaching aids. Therefore, in this advanced technological era, the author developed interactive instructional media for the local content subject (Mulok) of the Sasak language to facilitate teachers and students in the learning process, enabling them to understand the material more quickly so that learning becomes more interesting and easier to comprehend. This media development begins with a needs analysis process, followed by design based on the results of the analysis. The use of this media also helps teachers deliver material more effectively, thereby motivating students and preventing boredom.